Pengaruh Subtitusi Tepung Terigu Dengan Ubi Jalar Ungu (Ipomoea batatas Poiret) Dan Rumput Laut (Euchema cotonii) Terhadap Kualitas Mie Basah - Kining, Ekajayanti; Alvita, Livia Rhea; Husain, Halimah (Jurnal Gizi dan Kuliner (Journal of Nutrition and Culinary), 2021)
This research is an experimental research that aimed to find the best composition of purple sweet potato wet noodle between wheat flour, purple sweet potato and seaweed as food alternatives and determine the effect of ratio of flour and purple sweet potato by adding seaweed to the organoleptic quality (color, flavor, aroma and firmness), tensile strength and water content. The samples in this research were wheat flour, purple sweet potato (Ipomoea batatas Poiret) and seaweed (Euchema cotonii). The research outcome data were analyzed by using analysis of variance (ANOVA) with 2 factorial i.e the ratio between flour and sweet potato (A) with 3 levels : (100% wheat flour: 0% sweet potato), (60% wheat flour: 40% sweet potato), and (50% wheat flour: 50% sweet potato) and the addition of seaweed (B) with 2 level, ie without the addition of seaweed and seaweed with the addition of 6 g. Ratio of wheat flour with purple sweet potato had highly significant effect on organoleptic (color, flavor, aroma and firmness), tensile strength and water content of the resulting wet noodle. The addition of seaweed had highly significant effect on the organoleptic color but did not significant effect on water content, tensile strength, organoleptic taste, aroma and firmness. Ratio of wheat flour and 60% purple sweet potato: 40% give better results in the manufacture of purple sweet potato wet noodles.